Central Role of Reverting Mutations in HLA Associations with Human Immunodeficiency Virus Set Point - Matthews, Philippa C.; Prendergast, Andrew; Leslie, Alasdair; Crawford, Hayley; Payne, Rebecca; Rousseau, Christine; Honeyborne, Isobella; Carlson, Jonathan M.; Kadie, Carl; Brander, Christian; Bishop, Karen; Mlotshwa, Nonkululeko; et al. (Journal of Virology, 2008)
Much uncertainty still exists over what T-cell responses need to be induced by an effective human immunodeficiency virus (HIV) vaccine. Previous studies have hypothesized that the effective CD8 T-cell responses are those driving the selection of escape mutations that reduce viral fitness and therefore revert posttransmission. In this study, we adopted a novel approach to define better the role of reverting escape mutations in immune control of HIV infection. This analysis of sequences from 710 study subjects with chronic C-clade HIV type 1 infection demonstrates the importance of mutations that impose a fitness cost in the control of viremia. Consistent with previous studies, the viral set points associated with each HLA-B allele are strongly correlated with the number of Gag-specific polymorphisms associated with the relevant HLA-B allele (r 0.56, P 0.0034). The viral set points associated with each HLA-C allele were also strongly correlated with the number of Pol-specific polymorphisms associated with the relevant HLA-C allele (r 0.67, P 0.0047). However, critically, both these correlations were dependent solely on the polymorphisms identified as reverting. Therefore, despite the inevitable evolution of viral escape, viremia can be controlled through the selection of mutations that are detrimental to viral fitness. The significance of these results is in highlighting the rationale for an HIV vaccine that can induce these broad responses.